Outcomes of Bone Marrow-Derived Mononuclear Cell Transplantation for Patients in Persistent Vegetative State After Drowning: Report of Five Cases - Nguyen Thanh Liem; Nguyen Thanh Liem; Vu Duy Chinh; Dam Thi Minh Phuong; Dam Thi Minh Phuong; Ngo Van Doan; Nicholas R. Forsyth; Michael Heke; Phuong Anh Nguyen Thi; Xuan-Hung Nguyen; Xuan-Hung Nguyen (Frontiers in Pediatrics, 2020)
Aim: Anoxic brain injury (ABI) due to non-fatal drowning may cause persistent vegetative state (VS) that is currently incurable. The aim of this paper is to present the safety and feasibility of autologous bone marrow-derived mononuclear cell (BMMNC) transplantation in five drowning children surviving in persistent VS.Methods: We used BMMNC as a novel candidate therapeutic tool in a pilot phase-I study for five patients affected by neurological sequelae after near-death drowning. Autologous BMMNCs were freshly isolated using Ficoll gradient centrifugation then infused intrathecally to five patients. The number of transplantation varied from two to four times depending on the motor function improvement of patient after transplantation. Clinical therapeutic effects were evaluated using gross motor function measure and muscle spasticity rating scales, cognitive assessments, and brain MRI before and after cell administrations.Results: Six months after BMMNC transplantation, no serious complications or adverse events were reported. All five patients displayed improvement across the major parameters of gross motor function, cognition, and muscle spasticity. Three patients displayed improved communication including the expression of words. In particular, one patient remarkably reduced cerebral atrophy, with nearly normal cerebral parenchyma after BMMNC transplantation.Conclusions: Autologous BMMNC transplantation for the treatment of children in persistent VS after drowning is safe, feasible, and can potentially improve motor function and cognition and reduce muscle spasticity. These results pave the way for a future phase II clinical trial to evaluate the efficacy of the therapy.